1985
DOI: 10.1070/pu1985v028n01abeh003632
|View full text |Cite
|
Sign up to set email alerts
|

Deep and resonance states in AIVBVIsemiconductors

Abstract: The problem of quantum dice rolling (DR)-a generalization of the problem of quantum coin flipping (CF) to more than two outcomes and partiesis studied in both its weak and strong variants. We prove by construction that quantum mechanics allows for (i) weak N -sided DR admitting arbitrarily small bias for any N and (ii) two-party strong N -sided DR saturating Kitaev's bound for any N . To derive (ii) we also prove by construction that quantum mechanics allows for (iii) strong imbalanced CF saturating Kitaev's b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
132
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(149 citation statements)
references
References 5 publications
16
132
0
1
Order By: Relevance
“…The matching between the L-pockets' Luttinger volumes and Hall numbers implies that PbTe, up to a carrier concentration of p H = (9.4 ± 0.6) × 10 19 cm −3 , is single band, that is, all the carriers contributing to conduction belong to the L band. This result implies that the band offset between the L and Σ valence band maxima is underestimated in our DFT calculations, as well as all previously published band-structure calculations 8,13,33,34,[42][43][44][45][46] , which predict the appearance of the Σ band at a hole concentration of the order of p ≈ 1 × 10 19 cm −3 . The evolution of the three high symmetry L-pocket cross-sectional areas, in frequency units (f min , f max and f [100] ), with Hall number is plotted in figure 13.…”
Section: A Fermi Surface Topologysupporting
confidence: 59%
See 1 more Smart Citation
“…The matching between the L-pockets' Luttinger volumes and Hall numbers implies that PbTe, up to a carrier concentration of p H = (9.4 ± 0.6) × 10 19 cm −3 , is single band, that is, all the carriers contributing to conduction belong to the L band. This result implies that the band offset between the L and Σ valence band maxima is underestimated in our DFT calculations, as well as all previously published band-structure calculations 8,13,33,34,[42][43][44][45][46] , which predict the appearance of the Σ band at a hole concentration of the order of p ≈ 1 × 10 19 cm −3 . The evolution of the three high symmetry L-pocket cross-sectional areas, in frequency units (f min , f max and f [100] ), with Hall number is plotted in figure 13.…”
Section: A Fermi Surface Topologysupporting
confidence: 59%
“…Such impurity dopants have been shown to enhance the thermoelectric figure of merit, zT , from 0.8 to 1.4 for the case of sodium doping [4][5][6] , and to 1.5 for doping with thallium 4,7 . Tl is also the only dopant known to date that leads to a superconducting ground state in PbTe; remarkably its maximum critical temperature of T c =1.5 K is almost an order of magnitude higher than other superconducting semiconductors with similar carrier density [8][9][10][11][12] . Understanding the physical origin of these enhanced properties and their dependence on the choice of dopant chemistry requires a detailed knowledge of the electronic structure, in particular its evolution with changes in dopant and carrier concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Potential ways to improve the power factor are through increasing the Seebeck coefficient (S) via band modification 4 or engineering 5 , energy barrier filtering [6][7][8] , additional carrier pocket 9 , and resonant states 10 , or enhancing the mobility such as modulation doping 11 . Among these possibilities, resonant states and additional carrier pockets have led to net increased ZT values via the power factor enhancements 9,10 . In contrast, many methods have been found to be effective in reducing lattice thermal conductivity, for example, alloy scattering, boundary scattering, nanocomposites or nanoinclusion routes, etc.…”
Section: Broader Contextmentioning
confidence: 99%
“…22,23 The effect of Tl substitution for Pb in PbSe has also been discussed in the same context of resonance levels. 24 Schlichting and Gobrecht studied the mobility of n and p type PbSe from 0.3 to 800 K and for carrier densities ranging from 10 16 to 10 20 cm −3 by controlling the stoichiometry of Pb and Se. 25 It was concluded that phonon scattering dominates the temperature region of interest for thermoelectric applications.…”
Section: -8mentioning
confidence: 99%